Mutations in FLNB cause boomerang dysplasia. Issue 7 (1st July 2005) - Bicknell, L S; Morgan, T; Bonafé, L; Wessels, M W; Bialer, M G; Willems, P J; Cohn, D H; Krakow, D; Robertson, S P
Abstract : Boomerang dysplasia (BD) is a perinatal lethal osteochondrodysplasia, characterised by absence or underossification of the limb bones and vertebrae. The BD phenotype is similar to a group of disorders including atelosteogenesis I, atelosteogenesis III, and dominantly inherited Larsen syndrome that we have recently shown to be associated with mutations in FLNB, the gene encoding the actin binding cytoskeletal protein, filamin B. We report the identification of mutations in FLNB in two unrelated individuals with boomerang dysplasia. The resultant substitutions, L171R and S235P, lie within the calponin homology 2 region of the actin binding domain of filamin B and occur at sites that are evolutionarily well conserved. These findings expand the phenotypic spectrum resulting from mutations in FLNB and underline the central role this protein plays during skeletogenesis in humans.